1986
DOI: 10.1080/00039896.1986.9936705
|View full text |Cite
|
Sign up to set email alerts
|

Biliary and Urinary Excretion of Metals in Humans

Abstract: Fifteen metals (lead, cadmium, arsenic, inorganic mercury, organic mercury, iron, manganese, magnesium, chromium, zinc, copper, nickel, cobalt, tin, and aluminum) were determined in the hepatic bile and urine collected simultaneously from three Japanese individuals (2 males, 1 female). The presence of these metals was classified as follows: hepatic biliary concentrations were higher than urinary concentrations (lead, arsenic, and iron); urinary concentrations were higher than hepatic biliary concentrations (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The rate of urinary excretion following the intravenous administration of cobalt chloride was very rapid and the majority of the dose was eliminated by 12 h. The total fecal elimination was approximately 10% of the dose, and supported the finding that cobalt can be secreted in the bile in animals and in humans (Ulrich & Copp, 1950;Stelzer & Klaassen, 1985;Ishihara & Matsushiro, 1986). Gregus and Klaassen (1986) found that cobalt secreted in the bile was not reabsorbed by the small intestine.…”
supporting
confidence: 64%
“…The rate of urinary excretion following the intravenous administration of cobalt chloride was very rapid and the majority of the dose was eliminated by 12 h. The total fecal elimination was approximately 10% of the dose, and supported the finding that cobalt can be secreted in the bile in animals and in humans (Ulrich & Copp, 1950;Stelzer & Klaassen, 1985;Ishihara & Matsushiro, 1986). Gregus and Klaassen (1986) found that cobalt secreted in the bile was not reabsorbed by the small intestine.…”
supporting
confidence: 64%
“…From the results presented it appears that Cu homeostasis is maintained through control of only endogenous excretion and not absorption. Although the present study does not include data on urinary output, it has been reported that this form of excretion is minimal (Ishihara & Matsushiro, 1986) and is not dependent on dietary Cu intake. Turnlund et al (1989Turnlund et al ( , 1998 have performed two dietary intervention studies with male volunteers, feeding Cu levels similar to those used in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…Cd excret includes Cd from either of two sources, namely, Cd in the bile, 14) which originates both in Cd currently absorbed and Cd moved from the organs storing Cd, such as the liver and kidneys, and Cd from peeled epithelial cells and other intrinsic sources (Fig. 1).…”
Section: Definition Of CD Uptake and Cd Intake-output Balancementioning
confidence: 99%
“…Itai-Itai disease is one disastrous example of chronic Cd poisoning. Food is the main source of Cd intake for non-occupationally exposed people, and the average dietary Cd intake by the Japanese general population was recently calculated as 28 µg/d 1) , much higher than that in other countries; e.g., 9.9 in China 2) , 7.3 in Malaysia 3) , 14.5 in Finland 4) , 8.3 in Sweden 5) and 9 to 10 in Germany 6) . In Japan, rice and shellfish are the major sources of Cd intake, and other foods sold in Japanese markets contain a very wide range of Cd concentrations 7) .…”
mentioning
confidence: 99%